Functional outcome of anterior cruciate ligament (ACL) reconstruction: comparison of bone-patella tendon-bone (BPTB) vs. Hamstring graft - Raj, Jeffrey Jaya; Nik Mohd Najmi, Nik Mohd Fatmy; Hamdan, Mohammad Amirrudin; Che Ahmad, Aminudin; Zulkifly, Ahmad Hafiz (IIUM Medical Journal Malaysia, 2016)
Introduction: This is a cross-sectional study to evaluate the functional outcome of ACL Reconstruction between BPTB and hamstring graft who underwent ACL Reconstruction between January to June 2012 at our institution. Methods: Functional IKDC scoring was done pre-operatively, at 6 months and one year. Arthrometric measurements were taken using KT2000. Lysholm score and SF-36 were assessed at one year. Resuts: All patients are male, mean age is 29 (21 to 37 years old). 21.4% patients from patella BPTB group and 13% of hamstring group had anterior knee pain. 50% of patients from both groups complained of numbness over operative site. Average time return to pre-injury sports activity for BPTB group was 7.9 months, whereas for hamstring group was 8.3 months. KT-2000 measurements revealed an average side to side laxity difference average of 6.6mm in BPTB group and 7.9mm in hamstring group. Pivot shift were negative at 6 months in all patients. IKDC knee scoring significantly improved from grade C or D to grade B in 82% of BPTB group and 63% in hamstring group one year post operatively. There were no difference between both groups in terms of SF-36, Lysholm score and knee range of motion. Conclusions: There are no difference in functional outcome and lysholm knee score between the two groups although there is a discrepancy of IKDC score and arthrometric measurement at one year. Although both groups have moderate anterior laxity after one year, but they are asymptomatic and able to go back to preinjury sports activities.